1995
DOI: 10.1159/000211347
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Lipogenesis in the Isolated Hamster Flank Organ through Clofibric Acid

Abstract: The hamster flank organ model was used to measure the effects of clofibric acid on the in vitro uptake of sodium [1-14C] acetate into lipids. Clofibric acid produces a dose-dependent inhibition of lipogenesis in the hamster flank organ in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…This can be attributed to our different models; the organ maintained sebaceous gland will preserve a greater degree of differentiation than the primary culture. In support of this conclusion Strauss et al 34 have shown that the oral administration of ETYA to human male volunteers significantly reduced sebum secretion, and Venencie et al 35 demonstrated that clofibric acid produced a dose-dependent inhibition of lipogenesis in the hamster flank organ in vitro. Thus, one might postulate that structures that are missing in sebocyte monolayers but are present in whole organ cultures may be involved in PPAR agonist activity.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This can be attributed to our different models; the organ maintained sebaceous gland will preserve a greater degree of differentiation than the primary culture. In support of this conclusion Strauss et al 34 have shown that the oral administration of ETYA to human male volunteers significantly reduced sebum secretion, and Venencie et al 35 demonstrated that clofibric acid produced a dose-dependent inhibition of lipogenesis in the hamster flank organ in vitro. Thus, one might postulate that structures that are missing in sebocyte monolayers but are present in whole organ cultures may be involved in PPAR agonist activity.…”
Section: Discussionmentioning
confidence: 90%
“…In support of this conclusion Strauss et al 34 . have shown that the oral administration of ETYA to human male volunteers significantly reduced sebum secretion, and Venencie et al 35 . demonstrated that clofibric acid produced a dose‐dependent inhibition of lipogenesis in the hamster flank organ in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…[167] has shown that the oral administration of ETYA to human male volunteers significantly reduced sebum secretion, and Venencie et al. [168] demonstrated that clofibric acid produced a dose‐dependent inhibition of lipogenesis in the hamster flank organ in vitro . Thus, one might postulate that structures that are missing in sebocyte monolayers but are present in whole organ cultures may be involved in PPAR agonist activity.…”
Section: Peroxisome Proliferator Activated Receptorsmentioning
confidence: 99%
“…All of these organelles are prominent in sebocytes (Goldenberg et al, 1975;Mednieks et al, 1991). Some PPAR subtypes have been detected in rat sebaceous glands and epidermis (Braissant et al, 1996), but in vivo studies have not shown the PPAR activators clofibric acid (Venencie, 1995) or eicosatetraynoic acid (Strauss et al 1967) to stimulate sebum formation. In spite of these inconclusive data, we have found in a preliminary study that the PPARγ activator BRL induced preputial sebocytes to differentiate as lipid-forming colonies in culture (Rosenfield et al, 1998).…”
mentioning
confidence: 99%